The South Asian Canadian Digital Archive Thesaurus: Thesaurus Construction for the South Asian Canadian Diaspora - Berg, Magnus; Bains, Satwinder Kaur; Suri, Sadhvi (KULA, 2022)
The South Asian Canadian Digital Archive (SACDA) is a soon-to-be-released digital repository developed by the South Asian Studies Institute at the University of the Fraser Valley, located in Abbotsford, British Columbia, Canada. SACDA partners with memory institutions, individuals, families, and organizations to digitize, describe, and provide online public access to heritage materials created by, or relevant to, the South Asian Canadian diaspora. This project report will detail how SACDA is building a customized thesaurus to classify its digitized archival holdings, augment existing subject headings and thesauri, and fill in taxonomical gaps. Building on prior work done by alternative thesauri like the Homosaurus, Association for Manitoba Archives Indigenous Subject Headings, Australian Institute of Aboriginal and Torres Strait Islander Studies (AIATSIS) Thesauri, and the International Thesaurus of Refugee Terminology, among others, the SACDA thesaurus intends to fill in a vital gap in South Asian Studies subject control, particularly from a Canadian perspective.